Pengaruh Komunikasi, Budaya Organisasi dan Kompetensi terhadap Efektivitas Kerja : Studi Kasus pada Karyawan Hotel Mercure Serpong Alam Sutera di Tangerang Selatan - Mohammad Rafdhi Ashari; Aris Wahyu Kuncoro (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
This research aims to analyze the influence of communication skills, organizational culture, and the Competennce on the work effectiveness of Hotel Mercure Serpong Alam Sutera employees. Sampling using a non-probability sampling technique with a saturated sampling type was 63 employees of the Mercure Serpong Alam Sutera Hotel. Data was collected through questionnaires and analyzed using multiple regression analysis. The research results show that organizational culture and competency variables have a significant positive influence on work effectiveness. Meanwhile, the communication variable cannot have a significant influence on work effectiveness at the Mercure Serpong Alam Sutera Hotel.